CONDITIONS FOR COMPETENCE OF THE TEACHER OF PHYSICAL EDUCATION AND THE METHODOLOGY OF ITS ORGANIZATION (Neo Scientific Peer Reviewed Journal, 2024)
In this article, the author expresses his opinion on the scientific-theoretical aspects of the competent approach and its importance in developing the creativity of the students of physical culture in their future professional pedagogical activities.